Therapeutic Suppression of FAK-AKT Signaling Overcomes Resistance to SHP2 Inhibition in Colorectal Carcinoma - Li, Ye; Yuan, Yuncang; Zhang, Fan; Guo, Aizhen; Cao, Fuao; Song, Mengmeng; Fu, Yating; Xu, Xiaowen; Shen, Hao; Zheng, Shangyong; Pan, Yamin; Chang, Wenjun (Frontiers in Pharmacology, 2021)
SHP2 mediates signaling from multiple receptor tyrosine kinases (RTKs) to extracellular signal-regulated kinase (ERK) and Ser and Thr kinase AKT, and its inhibitors offer an unprecedented opportunity for cancer treatment. Although the ERK signaling variation after SHP2 inhibition has been well investigated, the AKT signaling variation in colorectal carcinoma (CRC) is still unknown. Therefore，we performed immunohistochemistry and bioinformatics analyses to explore the significance of p-SHP2 in CRC. A panel of CRC cell lines with the SHP2 inhibitor, SHP099, was used to assess the effects on viability and signaling. The inhibitors of AKT and focal adhesion kinase (FAK) signaling were examined in combination with SHP099 as potential strategies to enhance the efficacy and overcome resistance. Frequent resistance to the SHP2 inhibitor was observed in CRC cells, even in those without RAS mutations. We observed rapid adaptive reactivation of the AKT pathway in response to SHP2 inhibition, possibly driven by the reactivation of RTKs or released p-FAK. High baseline p-FAK may also be associated with CRC cell resistance to SHP2 inhibition. Co-inhibition of FAK abrogated the feedback reactivation of AKT in response to SHP2 inhibition. Moreover, the combined inhibition of SHP2 with AKT or FAK resulted in sustained AKT pathway suppression and improved antitumor efficacy in vitro and in vivo. Our study found that reactivation of the AKT pathway is a key mechanism of adaptive resistance to SHP2 inhibition, highlighting the potential significance of AKT and FAK inhibition strategies to enhance the efficacy of SHP2 inhibitors in CRC treatment.